A Little Bit More Far than Mexico: How 3- and 4-year Old Jewish Children Understand Israel. Issue 1 (2nd January 2021) - Applebaum, Lauren; Hartman, Anna; Zakai, Sivan
ABSTRACT: This study examines how 3- and 4-year-old Jewish children think and feel about Israel. The research, conducted as a collaboration between scholars and practitioner-researchers who work in Jewish early childhood centers, draws upon group interviews, elicitation/provocation exercises, a drawing task, and teacher documentation to investigate how some of the youngest learners in Jewish educational settings conceive of Israel. We found that 3- and 4-year-old Jewish children think about Israel as a foreign country with its own customs, landmarks, and language. They also think about Israel as a distinctly Jewish place, with a special role in Jewish traditions and stories. We found no evidence that 3- and 4-year-old children reflect on Israel as a place of personal meaning for their own Jewish lives. This absence challenges both the theory and practice of Israel education in the early childhood setting.